2016
DOI: 10.18533/ijbsr.v5i12.850
|View full text |Cite
|
Sign up to set email alerts
|

Performance Contracting As a Strategy for Enhanced Employee Commitment: A Case of the Vocational Training Centre Sikri, Kenya

Abstract: <p>Literature on the relationship between performance contracting and employee commitment in tertiary special needs institutions in Kenya is dearth. In addition to this, majority of these past researchers who have attempted to investigate these variables have concentrated on performance contracting implementations in state corporations with few studies done on its effectiveness on service delivery in tertiary institutions. This study therefore sought to investigate the link between performance contractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
4
4
0
Order By: Relevance
“…According to the results, empowering employees through provision of adequate resources and rewarding them according to their achievement remains a panacea for improved productivity. This revelation seems to concur with several studies (Kago, 2014;Kemboi, 2015;Nganyi et al, 2014;Nyaigo et al, 2013). Kago (2014) found that performance contracting influenced both enterprise and managerial performance at the State Corporations in Kenya while Kemboi (2015) revealed a positive relationship between employee commitment, performance contracting and employee productivity among vocational training centers in Kenya.…”
Section: Performance Contracting and Employee Productivitysupporting
confidence: 93%
“…According to the results, empowering employees through provision of adequate resources and rewarding them according to their achievement remains a panacea for improved productivity. This revelation seems to concur with several studies (Kago, 2014;Kemboi, 2015;Nganyi et al, 2014;Nyaigo et al, 2013). Kago (2014) found that performance contracting influenced both enterprise and managerial performance at the State Corporations in Kenya while Kemboi (2015) revealed a positive relationship between employee commitment, performance contracting and employee productivity among vocational training centers in Kenya.…”
Section: Performance Contracting and Employee Productivitysupporting
confidence: 93%
“…Notable challenges or gaps in the implementation of performance contracts processes in the public sector include inadequate capacity development, and lack of awareness of performance contracts meaning and purpose by the middle and lower-level personnel in most organizations (Gichini, 2015). According to Kemboi (2020), other challenges that have greatly hindered implementation of performance contracts in Kenya include lack of leadership, organizational culture, financial constraints and resistance to change. He opines that lack of training and motivation among the workers contributes a lot to low levels of achievement of set targets and goals.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In recommendation, pragmatic efforts to enhance employees' job capabilities through training, improved working conditions and general welfare in order to elicit job satisfaction and motivation for increased productivity. Kemboi et al (2013) examined staff welfare as an antecedent to service delivery among civil servants in Kenya a case study of Nandi County. The study adopted explanatory research design.…”
Section: Workers Compensation Programmesmentioning
confidence: 99%